2019
DOI: 10.1111/jsr.12903
|View full text |Cite
|
Sign up to set email alerts
|

Exercise before bed does not impact sleep inertia in young healthy males

Abstract: Sleep inertia is the transitional state marked by impaired cognitive performance and reduced vigilance upon waking. Exercising before bed may increase the amount of slow‐wave sleep within the sleep period, which has previously been associated with increased sleep inertia. Healthy males (n = 12) spent 3 nights in a sleep laboratory (1‐night washout period between each night) and completed one of the three conditions on each visit – no exercise, aerobic exercise (30 min cycling at 75% heart rate), and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…A recent study by our team investigated the possibility whether athletes exercising prior to their night-time sleep periods would exhibit greater amounts of slow-wave sleep in their night-time sleep period, which could subsequently impact the severity and/or duration of sleep inertia. 98 This hypothesis could potentially mean that athletes may be more susceptible to the impacts of sleep inertia given (in most cases) that their level of exercise is greater than the general population. 98 However, this study concluded that exercise of a moderate-intensity performed 90 min before bed did not negatively impact sleep inertia and there was no relationship between the amount of slow wave sleep in the preceding sleep period and sleep inertia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by our team investigated the possibility whether athletes exercising prior to their night-time sleep periods would exhibit greater amounts of slow-wave sleep in their night-time sleep period, which could subsequently impact the severity and/or duration of sleep inertia. 98 This hypothesis could potentially mean that athletes may be more susceptible to the impacts of sleep inertia given (in most cases) that their level of exercise is greater than the general population. 98 However, this study concluded that exercise of a moderate-intensity performed 90 min before bed did not negatively impact sleep inertia and there was no relationship between the amount of slow wave sleep in the preceding sleep period and sleep inertia.…”
Section: Discussionmentioning
confidence: 99%
“… 98 This hypothesis could potentially mean that athletes may be more susceptible to the impacts of sleep inertia given (in most cases) that their level of exercise is greater than the general population. 98 However, this study concluded that exercise of a moderate-intensity performed 90 min before bed did not negatively impact sleep inertia and there was no relationship between the amount of slow wave sleep in the preceding sleep period and sleep inertia. 98 Therefore, it seems unlikely that athletes have a greater likelihood of experiencing enhanced duration and/or severity of sleep inertia compared to non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The participants refrained from exercising on study days apart from the designated exercise period. Prior to going to bed, electrodes were attached to the participants' head and face using a standard montage, reported elsewhere (Vincent et al., 2019b). At 24:00 hours lights were turned off and participants went to sleep.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were required to have habitual bedtimes and wake times within 2 hr of the study bedtimes and wake times (bedtimes between 22:00 and 24:00 hours and wake times between 06:00 and 09:00 hours). These are common exclusion criteria for sleep or exercise studies because they are known confounds for sleep or exercise interventions (Kovac, Vincent et al, 2020b;Vincent et al, 2019aVincent et al, , 2019b. During the recruitment process, 21 out of 41 participants did not satisfy the exclusion criteria and were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…Together, these data suggest that the sleep quality benefits of chronic exercise training may be more related to consistently performing exercise rather than the time of the exercise bout. Notably, the majority of sleep and exercise research has been conducted in healthy young men, many of whom are highly trained athletes [97][98][99][100][101][102][103]. Therefore, a major gap in the current literature is a lack of studies in populations that are translatable to the overall population.…”
Section: Comparison Of Morning Vs Evening Exerciseexercise Trainingmentioning
confidence: 99%